Optimalisasi Operasional Layanan dan Integrasi Sistem pada Arsitektur Perusahaan PT X melalui Penerapan TOGAF ADM - Benedicta, Laurence; Aprikasari, Manda; Rachmatsyah, Agus Dendi; Atmojo, Wahyu Tisno (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
This research discusses the application of the TOGAF ADM method in modelling X Ltd,which operates in the field of printing and book publishing services. X Ltd facesoperational challenges that are still manual and not fully integrated with the system sothat the service operational process becomes ineffective in terms of time. This researchaims to design an integrated architecture, including business process architecture,application and data architecture, and technology architecture. The research method usesa qualitative approach by conducting interviews with two sources from X Ltd to analyzecurrent operations. The results show that TOGAF ADM can help X Ltd Optimizes itsoperational system, accelerates data management, publishing books, and improvingcustomer service, and facilitating adaptation to changes through new system architecturemodelling.